Konsep Dasar Pendidikan Islam - Fatihatun Nadliroh (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
Islamic education has a very strategic role in forming a generation that is not only intellectually intelligent, but also has faith and noble character. Education in Islam is designed to develop all human potential, both physical, intellectual, spiritual and moral, aiming not only for worldly life, but also happiness in the afterlife. In this context, Islamic education combines religious values ​​with modern knowledge to create humans who are able to adapt to the challenges of the times without forgetting their religious identity and teachings. This paper aims to explore the concept of Islamic education from various perspectives, including philosophical aspects, objectives, curriculum, teaching methods, as well as their implementation in modern life. By deepening understanding of Islamic education, it is hoped that solutions will emerge to the global challenges faced by Muslims today, such as moral crises, value disorientation, and an imbalance between mastery of knowledge and spirituality. This paper also highlights the importance of updating the curriculum and teaching methods in accordance with technological developments and the demands of the times, without ignoring fundamental Islamic values. Through this study, it is hoped that readers can understand more deeply how Islamic education can play a role in forming a generation that is not only physically intelligent. intellectual, but also have strong moral and spiritual integrity, so that they are able to contribute to creating a better civilization in the future.